Efektivitas Phase Change Material Sebagai Media Penyimpanan Energi Termal Pada Kotak Pendingin - Nurhidayanti; Sabiqunassabiqun; Ady Saputra , Alfian (Jurnal Permadi : Perancangan, Manufaktur, Material dan Energi, 2025)
The challenge of energy efficiency in cooling systems has driven exploration into thermal energy storage technologies using Phase Change Materials (PCM). This study aims to evaluate the thermal performance of two types of PCM—liquid-phase propylene glycol (PG) and solid-phase paraffin wax (PW)—in passively maintaining the temperature inside a cooling box. The experimental setup involved a Styrofoam-based cooling chamber lined with aluminum, where both PCMs were placed in identical containers. Temperature data for the internal chamber, PCM, and ambient air were recorded over 90 minutes using thermocouples and a data logger. Key parameters analyzed included temperature distribution, absorbed heat quantity and rate, and thermal efficiency of each PCM. The results indicate that PCM PG exhibits superior thermal performance, demonstrated by a higher heat absorption capacity (783.38 J), more consistent heat transfer rate, and greater maximum thermal efficiency compared to PCM PW (715.10 J). Therefore, PCM PG is recommended as a more promising material for efficient and sustainable passive thermal energy storage systems.